Geochemistry of Basaltic Merbabu Volcanic Rocks, Central Java, Indonesia - Sri Mulyaningsih; Godang Shaban (Indonesian Journal on Geoscience, 2020)
DOI: 10.17014/ijog.7.2.161-178The studied area is located along the hiking track of Kajor - Selo, the south flank of Merbabu Volcano, Central Java, Indonesia. Olivine basalt and augite-rich basalt compose the volcanic rocks. A geochemical study recognizes these basalts which tend to originate from the product of tholeiitic magma, in terms of transitional enriched mantle source. It is interpreted to have been formed as primary magma that mixed later with higher degrees of partial melting with a mantle wedge. Both fl uid and melt were derived from the mixing of lower active continental margin and subducting oceanic slab. This study also shows general trends of increasing incompatible elements, i.e. Rb, Ba, Pb2+, and Sr as LIL trace elements and Th, U, Nb, Ce, Zr, Hf, Nb, and Ta as HFS element comparing to basaltic andesites exposed at Thekelan, they show decreasing compatible of MgO, Fe2O3*, Al2O3, CaO, TiO2, Ni, Sr, and Ba in line with increasing SiO2. It was fractional crystallization process, shown by the slightly wide variation of Rb/Zr and La/Sm that indicates random crustal contamination.